Assessing the impact of high blood pressure referrals on hypertension awareness and management, BMI, and blood pressure values in adult Samoans 2010–2019. (16th November 2020) - Rivara, Anna C.; Pomer, Alysa; Naseri, Take; Reupena, Muagututia Seifuiva; Viali, Satupaitea; Choy, Courtney C.; McGarvey, Stephen T.; Hawley, Nicola L.
Abstract: The Samoan population has experienced rapid increases in the prevalence of non-communicable diseases (NCDs) and NCD risk factors over the last 30 years. However, understanding how increased awareness and treatment of these conditions in reducing disease burden remains understudied. Using data from a longitudinal study (2010–2019) of cardiometabolic health among Samoan adults, we assess the impact of a referral for elevated blood pressure (BP) on changes in BP, physician's diagnoses of hypertension and medication use, body mass index (BMI), and other risk factors for elevated BP. Analyses compared adult Samoans ( n  = 328) who in 2010 either (1) received a referral for elevated BP (BP ≥ 140/90 mmHg) or (2) had measured BP indicative of pre-hypertension (BP ≥ 120/80 mmHg) but were not referred. Data were analysed using linear and logistic regression, paired T- and McNemar's tests, and Wilcoxon Rank Sum assessments. Referrals in 2010 significantly increased the odds of reporting a physician's diagnosis of hypertension (OR 2.16; 1.18, 3.95) and hypertension medication use (OR 3.52; 1.86, 6.73) in 2018; however, referrals, medication use, and diagnoses were not associated with BP values or reduced odds of having elevated BP. Despite the referral having positive effects on hypertension-related health care, our results demonstrate that other factors are influencing effective BP/hypertension control. We advocate for greater engagement of health researchers with local health sector actors to improve the probability that researcher-provided health referrals will result in long-term health improvements.